Analysis of Factors Influencing Profit Increase of Women's Msmes in Suka Jaya Village - SAKTI, M. Handoko; GUSTETI, Yesi; ERMAWATI, Eka (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to analyze the influence of access to market information, entrepreneurial motivation, and entrepreneurial capability on the profit growth of women-owned MSMEs in Suka Jaya Village. The research is grounded in the reality that, despite the significant potential of women's MSMEs in rural economic development, they still face various structural and managerial barriers that can affect business performance, particularly in terms of profit improvement. This study employs a quantitative approach using a survey method through questionnaires distributed to 130 women MSME actors, selected using a saturated sampling technique. Data analysis was conducted using validity and reliability tests, multiple linear regression analysis, T-test, F-test, and coefficient of determination (R²). The results indicate that access to market information has a positive and significant effect on profit growth when tested partially. In contrast, entrepreneurial motivation and entrepreneurial capability do not have a significant partial effect. However, when tested simultaneously, all three independent variables significantly influence profit growth. The Adjusted R² value of 0.839 implies that the model can explain 83.9% of the variation in profit growth, while the remaining 16.1% is influenced by other factors not examined in this study. These findings highlight the crucial role of access to market information in enhancing the profitability of women's MSMEs and emphasize the need for strategic interventions to improve entrepreneurial capacity based on local data.